The good, the bad, and the ambivalent: A qualitative study of public perceptions towards energy technologies and portfolios in Germany. (January 2017) - Scheer, Dirk; Konrad, Wilfried; Wassermann, Sandra
Abstract: This paper investigates informed public preferences about electricity technologies and portfolios in Germany, qualitatively analyzing opinions, reasoning patterns and judgments of perceived risks and benefits among lay people. The authors developed and applied a 'mixed-method' focus group approach involving 130 participants in 15 focus groups throughout Germany. This research aimed to specify participants' attitudes and preferences regarding electricity technologies and portfolios ( evaluation categories ); comparatively assess these preferences ( technology/portfolio acceptance profiles ); and identify participants' decision-making strategies and processes ( decision rule typology ). The evaluation basis of people's preferences comprises nine evaluation categories including, among others, trust, national and household economics, and environmental and health impacts. When assessing preferences regarding electricity technologies and portfolios, two overriding results need to be emphasized: first, that selective evaluation patterns produce unique acceptance profiles, and second, that a shift occurs from heterogeneous towards homogeneous evaluation patterns. In relation to decision rules guiding people's preference-making, the research reveals multiple mechanisms are at work when people express preferences about electricity portfolios. Five decision rules were identified regarding how participants dealt with complex portfolio information processing and preference building. Highlights: The evaluation basis of people's preferences comprises nine evaluation categories. Evaluation patterns produce unique technology and portfolio acceptance profiles. Five generic decision rules guide people's preference-making. People make decisions in multiple ways using a variety of evaluation strategies. No 'one-size-fits-all' approach for creating insights into the public's approval or rejection of technologies.